Features of Structural and Phase Transformations in Layers of Ni–Pt–V Alloy on Silicon During Rapid Heat Treatment - Ja. А. Solovjov; P. I. Gaiduk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Using the methods of Rutherford backscattering, X-ray phase analysis, transmission electron microscopy and diffraction, the features of structural and phase transformations in layers of Ni–Pt–V alloy with a thickness of 30 nm on the surface of monocrystalline n-Si(111) under rapid heat treatment with incoherent constant-power light flux from quartz halogen lamps directed to the reverse side of the substrate for a duration of 7 s until a temperature of 350 to 500 °С is reached have been established. It is shown that under these conditions of heat treatment, the formation of NixSiy layers occurs, characterized by varying degrees of ordering (epitaxy). It was found that rapid heat treatment at a temperature of 350 °С is accompanied by a redistribution of nickel and silicon atoms to the composition ∼Ni3Si at the film-substrate interface with a decrease in the proportion of Si towards the surface with the formation of domains of the hexagonal (P321) phase of the β-Ni31Si12 silicide epitaxial to the substrate. Rapid heat treatment at temperature from 400 to 500 °С leads to a further diffusion redistribution of the reacting components to a composite composition of ∼Ni50Si50 and the formation of an orthorhombic (Pnma) phase of NiSi silicide having a transrotational degree of epitaxy. In this case, the ordered growth of NiSi silicide occurs on the epitaxial domains of β-Ni31Si12, which persist at the interface between the silicide and the substrate up to a temperature of 500 °С.